Efficient active set algorithms for solving constrained least squares problems in aircraft control allocation - Harkegard, O. (41st IEEE Conference on Decision and Control, 2002)
In aircraft control, control allocation can be used to distribute the total control effort among the actuators when the number of actuators exceeds the number of controlled variables. The control allocation problem is often posed as a constrained least squares problem to incorporate the actuator position and rate limits. Most proposed methods for real-time implementation, like the redistributed pseudoinverse method, only deliver approximate, and sometimes unreliable solutions. We investigate the use of classical active set methods for control allocation. We develop active set algorithms that always find the optimal control distribution, and show by simulation that the timing requirements are in the same range as for two previously proposed solvers.